Trapping of the transport-segment DNA by the ATPase domains of a type II topoisomerase - Ivan Laponogov (Nature Portfolio, 2018)
Type 2 topoisomerases alter DNA supercoiling by an ATP-dependent reaction involving DNA passage through a cleaved DNA duplex. Here the authors present the crystal structure of the ParE ATPase domains of S. pneumoniae topoisomerase IV, in complex with a captured DNA oligonucleotide.